El trauma de las matanzas estudiantiles en la serie Belascoarán de Paco Ignacio Taibo II y la película Roma de Alfonso Cuarón - Tosik, Magdalena (Studia Romanica Posnaniensia, 2026)
Within the framework of memory and trauma studies that in the recent years has been widely applied to investigate social, cultural, and economic aspects of human existence, this article is aimed to analyse the collective imaginary that stands behind the massacres of students in Mexico (Tlatelolco, 1968 and El Halconazo, 1971), presenting a psychoanalytical approach based on the premises retrieved from the sociocultural theory of trauma. By means of the latter, this work examines the memory of El Halconazo represented in the novels on Hector Belascoarán by Paco Ignacio Taibo II and in the movie Roma by Alfonso Cuarón. Taking into consideration the social and historical context of actual events and the emancipation processes that have taken place in Mexico in the 21st century, the article exposes the revision of the national imaginary related to the massacres, highlighting the importance of female protagonists.